2020
DOI: 10.1063/5.0014553
|View full text |Cite
|
Sign up to set email alerts
|

κ-Deformed quantum and classical mechanics for a system with position-dependent effective mass

Abstract: We present the quantum and classical mechanics formalisms for a particle with a position-dependent mass in the context of a deformed algebraic structure (named κ-algebra), motivated by the Kappa-statistics. From this structure, we obtain deformed versions of the position and momentum operators, which allow us to define a point canonical transformation that maps a particle with a constant mass in a deformed space into a particle with a position-dependent mass in the standard space. We illustrate the formalism w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 82 publications
(153 reference statements)
0
25
2
Order By: Relevance
“…In this paper we have shown that DDL quantum systems can reflect infinite distinct discrete energy levels under suitable form of position dependent mass. The model mass [15] and used by others [1,3,7,9]. It is worth mentioning that only this typical form of T can be derived [8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this paper we have shown that DDL quantum systems can reflect infinite distinct discrete energy levels under suitable form of position dependent mass. The model mass [15] and used by others [1,3,7,9]. It is worth mentioning that only this typical form of T can be derived [8].…”
Section: Discussionmentioning
confidence: 99%
“…It should be borne in mind that all the figures on PDM actually we have plotted with T i.e p 2 M = T . In order to convince the reader about our method [1,3], we consider two simple models as…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, effects of the gravitational field in quantum mechanics have been characterized by generalizations of the standard commutation relationship between the position and the linear momentum, giving place to the generalized uncertainty principles (GUP). [46][47][48][49][50][51][52][53] In this context, some theoretical frameworks have been developed to mimic the effect of the PDM by means of deformed algebraic structures. [51][52][53] One of these formulations is derived from a a) Electronic mail: bruno.costa@ifsertao-pe.edu.br b) Electronic mail: cardoso.genilson@outlook.com c) Electronic mail: ignacio.sebastian@ufba.br translation operator that causes non-additive displacements of the type Tγ (ε)|x = |x + (1 + γx)ε , being γ a deformation parameter with inverse length dimension.…”
Section: Introductionmentioning
confidence: 99%
“…[46][47][48][49][50][51][52][53] In this context, some theoretical frameworks have been developed to mimic the effect of the PDM by means of deformed algebraic structures. [51][52][53] One of these formulations is derived from a a) Electronic mail: bruno.costa@ifsertao-pe.edu.br b) Electronic mail: cardoso.genilson@outlook.com c) Electronic mail: ignacio.sebastian@ufba.br translation operator that causes non-additive displacements of the type Tγ (ε)|x = |x + (1 + γx)ε , being γ a deformation parameter with inverse length dimension. [54][55][56][57][58][59][60][61][62][63][64][65][66][67] This translation operator leads to a position-dependent linear momentum operator pγ that generates non-additive translations.…”
Section: Introductionmentioning
confidence: 99%